(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Ischemic stroke is a leading cause of mortality and long-term disability worldwide. This study investigated the relationship between ischemic lesion volume and localization, as determined by MRI and MR spectroscopy, and the severity of cognitive and psychoemotional impairments during early post-stroke recovery. Fifty-five patients aged 52–73 years with cortical and subcortical strokes were examined. Cognitive function was assessed using MMSE, and anxiety and depression were evaluated with HADS. Larger lesion volumes and subcortical localization were associated with greater cognitive deficits and higher anxiety and depression levels. MR spectroscopy revealed decreased NAA/Cr and increased Cho/Cr ratios in affected regions, correlating with clinical manifestations. These findings highlight the value of neuroimaging for predicting impairments and guiding personalized neurorehabilitation.